ANALISIS PERBANDINGAN HEADWAY DAN METODE PEMBAYARAN PADA JAKARTA MASS RAPID TRANSIT (MRT JAKARTA) DAN SINGAPORE MASS RAPID TRANSIT (MRT SINGAPURA) - Rahmawati, Roselina; Fatmawati, Leily; Mukhlisin, M.; Wicaksono, Teguh Mulyo; Megantoro, Alam; Setioko, Rafi; H, M. Luqmanul (Construction and Material Journal, 2024)
The global population growth increased by 0.88% at the end of 2022 compared to the previous year. Jakarta and Singapore, as two densely populated areas in Southeast Asia, need to pay extra attention to the need for infrastructure, including adequate transportation systems. One of the prominent transportation modes in both regions is Mass Rapid Transit (MRT). MRT is an urban rail-based transportation mode aimed at providing regular and sustainable public services. The MRT system excels in capacity, speed, and reliability compared to other transportation modes, as it operates on fully separated tracks. Despite both regions having MRT systems, there are differences in several aspects. This research is conducted using a qualitative method, applying techniques such as the analysis of literature. The differing aspects between the Jakarta MRT and the Singapore MRT are headway (time between trains) and payment methods. The Singapore MRT has a smaller headway compared to the Jakarta MRT. The shorter the time, the better the service. In terms of payment methods, the Singapore MRT predominantly implements a cardless payment system, in contrast to the Jakarta MRT. The Jakarta MRT still offers the purchase of Single Trip Tickets and Multi Trip Tickets.